Hubungan Antara Kepemimpinan Diri, Berbagi Pengetahuan, dan Perilaku Kerja Inovatif di Lembaga Pendidikan Tinggi - Vallery Imanuel Purba; Tanti Sugiharti (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This research explores the relationship between self-leadership, knowledge sharing, and innovative work behavior within higher education institutions. In the context of globalization and digitalization, innovation is essential for enhancing the competitiveness of educational entities. Self-leadership is pivotal as it motivates individuals to pursue goals independently, while knowledge sharing acts as a mediator that fosters collaboration and information exchange among individuals. The study employs a literature review methodology to analyze various relevant sources, revealing that the development of self-leadership and a culture of knowledge sharing significantly enhances innovative work behavior, ultimately contributing to improved educational quality and institutional competitiveness. The findings offer valuable insights for academic leaders aiming to cultivate an environment conducive to innovation.